2020
DOI: 10.1051/e3sconf/202020002020
|View full text |Cite
|
Sign up to set email alerts
|

Relationship analysis of vegetation structural properties and the aboveground carbon stock of mangrove forest

Abstract: Mangrove forests have important ecological functions as a controller of environmental quality in coastal areas and absorber of atmospheric carbon. The mangrove ecosystem has a unique vegetation structure which form vegetation zonation that consists of different forest stands characteristics and tree species. This study aims to analyze the relationship between vegetation structural properties and the estimated aboveground carbon (AGC) stock of mangrove forest in Bedul mangrove, Banyuwangi, East Java, Indonesia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Biomass, carbon stock, and sequestration showed a high correlation (r = 0.935-0.962) with basal area and mean tree diameter. A previous study has shown that biomass and carbon stock of mangroves in Bedul, Banyuwangi, East Java were positively correlated with mean diameter, tree height, and density (Purnamasari et al 2020). Additionally, the greater biomass of some dominant mangrove trees in various locations has been attributed to their height (Duke et al 2013).…”
Section: Relationship Between Stand Characteristics and Biomass Carbo...mentioning
confidence: 96%
See 1 more Smart Citation
“…Biomass, carbon stock, and sequestration showed a high correlation (r = 0.935-0.962) with basal area and mean tree diameter. A previous study has shown that biomass and carbon stock of mangroves in Bedul, Banyuwangi, East Java were positively correlated with mean diameter, tree height, and density (Purnamasari et al 2020). Additionally, the greater biomass of some dominant mangrove trees in various locations has been attributed to their height (Duke et al 2013).…”
Section: Relationship Between Stand Characteristics and Biomass Carbo...mentioning
confidence: 96%
“…The species contributing the highest carbon sequestration are typically correlated with older tree age, which in turn, results in larger tree diameter. This tree diameter, in a positive correlation, leads to higher aboveground carbon stocks (Purnamasari et al 2020). Furthermore, there is a positive correlation between tree age and diameter, tree age and height, and tree age and biomass (Cabuy 2015).…”
Section: Proportion Of Mangrove Species In Contributing To Carbon Seq...mentioning
confidence: 99%